2021
DOI: 10.1099/mgen.0.000561
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bat adenoviruses suggests co-evolution and host roosting behaviour as drivers for diversity

Abstract: Adenoviruses (AdVs) are diverse pathogens of humans and animals, with several dozen bat AdVs already identified. Considering that over 100 human AdVs are known, and the huge diversity of bat species, many bat AdVs likely remain undiscovered. To learn more about AdV prevalence, diversity and evolution, we sampled and tested bats in Cameroon using several PCR assays for viral and host DNA. AdV DNA was detected in 14 % of the 671 sampled animals belonging to 37 different bat species. There was a correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Notably, their analysis was based on the consistency between the host and the virus evolutionary tree topologies. We employed similar consistency-based methods that compared the topological structures of the host and virus evolutionary trees to further test for co-evolution ( 41 44 ). The results of the Global test achieved with Parafit and PACo software showed no evidence of co-evolution between the viruses of Respirovirus genus and their hosts (ParaFitGlobal = 6.099, P -value = 0.307; m 2 global value = 3.023, P -value = 0.118; where P -value < 0.05, indicates a significant coevolving relationship).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, their analysis was based on the consistency between the host and the virus evolutionary tree topologies. We employed similar consistency-based methods that compared the topological structures of the host and virus evolutionary trees to further test for co-evolution ( 41 44 ). The results of the Global test achieved with Parafit and PACo software showed no evidence of co-evolution between the viruses of Respirovirus genus and their hosts (ParaFitGlobal = 6.099, P -value = 0.307; m 2 global value = 3.023, P -value = 0.118; where P -value < 0.05, indicates a significant coevolving relationship).…”
Section: Resultsmentioning
confidence: 99%
“…We observed numerous cases of roost sharing by multiple bat species. While roost use by multiple species is not uncommon in bats, large multi-species aggregations may play an important role in viral evolution and diversity within bat populations [54][55][56][57][58]. Currently, bat species documented to roost in multi-species assemblages have largely been described to co-roost with 2-3 other bat species [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…We observed numerous cases of roost sharing by multiple bat species. While roost use by multiple species is not uncommon in bats, these large multi-species aggregations may play an important role in viral evolution and diversity within bat populations (Luis et al 2013, Furey et al 2016, Willoughby et al 2017, Ntumvi et al 2021. Currently, other bat species documented to roost in multi-species assemblages have largely been described to co-roost with 2-3 other bat species (Arita 1993, Geiselman & Younger 2020, Salinas-Ramos et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…We found that M. pumilus roosted with at least six other bat species in anthropogenic roosts, indicating high potential for interactions with other bat species. Mops pumilus is known to host a high diversity of viruses, including coronaviruses, flaviviruses, adenoviruses, and potentially filoviruses (Kading et al 2015, Goldstein et al 2018, Nziza et al 2020, Ntumvi et al 2021. Several of these viral families have high potential for recombination, meaning that these diverse roosts may facilitate viral evolution in anthropogenic environments (Chan et al 2013).…”
Section: Discussionmentioning
confidence: 99%